Respon Pertumbuhan dan Hasil Stek Batang Tomat (lycopersicum eesculentum Mill) Terhadap Ekstra Bawang Merah dan Madu - Farida Hanum; Putu Eka Pasmidi Ariati; Luh Putu Yuni Widyastuti; Normiana Himan (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2023)
The title of this research is “Growth Response and Yield of Tomato Stem Cuttings (lycopersicum eesculentum Mill) to Shallot and Honey Extracts. Tomato (Lycopersicum Eesculentum Mill) is a type of vegetable that has high demand in the market because it is liked by almost all Indonesian people. Cutting aims to optimize the formation of a new root system. This study used a randomized block design (RAK) with various concentrations of onion and honey extract as stimulants with 5 levels. B0M0 : Red onion extra concentration 0ml + 0 ml honey, B1M4 : 40ml red onion extra concentration + 60 ml honey, B2M3 : 60ml red onion extra concentration + 40 ml honey, B3M2: 80ml red onion extra concentration + 20 ml honey, B4M1 : Red onion extra concentration 20 ml + 80 ml honey, B5M0: 100 ml red onion extra concentration + 0 ml honey, B0M5: 0 ml red onion extra concentration + 100 ml honey. In the results of this study, all parameters gave the best results and for giving the concentration of onion and honey extract gave very good results, namely by giving a concentration of 60% or red onion extract 60 ml/40 ml of honey. The concentration of onion extract gave the highest plant value, namely plant height, number of leaves, number of branches, number of flowers planted, number of fruit planted, weight of fruit planted, fruit diameter.